PENGARUH PROFITABILITAS TERHADAP NILAI EMITEN SYARIAH DI INDONESIA - Prasetyo, Yoyok; Lestari, Rini; Rahayu, Yulianita; Nurlela, Yuli (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2022)
The main task of the management of a public company is to prosper the shareholders. This is reflected in the increase in the value of the company.This study was conducted to determine the effect of profitability, especially Return on Assets (ROA) and Return on Equity (ROE) on firm value. The method used in this research is a quantitative approach. Obtained a sample of 15 Islamic companies listed on the Indonesia Stock Exchange (IDX). The results showed that the independent variable Return on Assets (ROA) did not have a partial effect on the dependent variable of Islamic firm value, both Price to Book Value (PBV) and Tobin's Q. While the independent variable Return on Equity (ROE) had a partial effect. on the dependent variable of Islamic firm value, both Price to Book Value (PBV) and Tobin's Q. So that in order to prosper the shareholders, the management of public companies must try to increase the Return on Equity (ROE).